Exploring the Role of Facebook in Supporting Senior Entrepreneurs - Muhamad, Marlina; Abd Razak, Fariza Hanis; Haron, Haryani (UUM Press, 2025)
Senior entrepreneurs are increasingly turning to social media platforms, notably Facebook, to promote and grow their businesses. Despite often having limited technical skills, senior entrepreneurs recognize the benefits of using social media as an essential tool for business communication and marketing. While there may be initial resistance to adopting social media, its benefits for businesses are widely recognized, making it a valuable entrepreneurial tool, facilitating communication and marketing efforts. This area of research is significant due to the global rise in the aging population and the growing trend of seniors transitioning into entrepreneurship after reaching retirement age. This qualitative investigation employed semi-structured interviews complemented by observations to explore the use of Facebook among senior entrepreneurs. Ten participants were interviewed face-to-face, with observations conducted based on insights gathered from these interviews. The findings indicate that senior entrepreneurs utilize Facebook to a moderate extent, primarily constrained by their limited digital knowledge. However, numerous features on Facebook remain unexplored, presenting potential opportunities for further business innovation within this demographic. This investigation provides insights into the adaptation of senior entrepreneurs to social media, particularly Facebook, as a tool for enhancing their business activities